Upaya Peningkatan Pendidikan Karakter Melalui Kisah Teladan Pada Siswa Kelas 2 SD Islam Ulil Albab Kebumen - Fatimah, Annisa Nur; Safingi, Imam; Savitri, Yanuariva Agiel; Fatimah, Siti (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Character education has become a major focus in the modern education system. This study aims to analyze efforts to improve character education through the use of role models in grade 2 students of SD Islam Ulil Albab in Kebumen. The research method used was classroom action research which involved active participation from students for several cycles. In this study, researchers collected data through observation, interviews, and document analysis. The role models selected focus on character values ​​such as honesty, cooperation, responsibility, and respect. The results of the study show that the use of role models in learning can influence the improvement of student character education. The results of this study indicated a significant increase in student behavior in terms of positive attitudes, communication skills, and involvement in group activities. In addition, students also show improvement in understanding and applying the character values ​​taught through exemplary stories. This research provides recommendations for teachers and schools to integrate role models in learning as an effective strategy for improving student character education. By strengthening character values ​​in the learning process, students are expected to develop a positive attitude, responsibility, and better social awareness.